Visual and ocular effects from the use of flat-panel displays - Porcar, Esteban (Int J Ophthalmol, 2016)
AIM: To evaluate the prevalence of eye symptoms in a non-presbyopic population of video display unit (VDU) users with flat-panel displays. METHODS: One hundred and sixteen VDU users with flat-panel display from an urban population participated in the study; their ages ranging from 20 to 34y. There were 60 females and 56 males. An eye examination to rule out the presence of significant uncorrected refractive errors, general binocular dysfunctions and eye conditions was carried out. In order to determine and quantify the type and nature of eye symptoms, participants were asked to answer written questionnaire and the results were grouped by gender, age and number of hours a day spent using a VDU. RESULTS: Seventy-two percent of participants reported eye symptoms related to VDU use. Eye symptoms from moderate-to-severe were found in 23% of participants. The main symptom was moderate-to-severe tired eyes (14%); followed by sensitivity to bright lights (12%), blurred vision at far distances (10%), eyestrain or dry eye or irritated or burning eyes (9%), difficulty in refocusing from one distance to another or headache (8%) and blurred vision at near or intermediate distances (<4%). Eye symptoms were greater among females (P=0.005) and increased with VDU use, markedly above 6h spent using a VDU in a typical day (P=0.01). CONCLUSION: Significant eye symptoms relate to VDU use often occur and should not be underestimated. The increasing use of electronic devices with flat-panel display should prompt users to take appropriate measures to prevent or to relieve the eye symptoms arising from their use.